Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3855/jidc.10542
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial role of Lactobacillus species as potential probiotics against enteropathogenic bacteria in chickens

Abstract: Introduction: The emergence of antimicrobial resistance among bacterial community resulted in a ban on drugs as the growth promoter in poultry feed. This situation demands to explore alternatives as food supplements with health benefit to poultry. Therefore, probiotic microorganisms, which are considered as safe and possess various health benefits can be a choice. Present study was designed to explore the probiotic potential of the isolated lactobacillus species in chickens. Methodology: Out of 220 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…One of these bacteria is Lactobacillus sakei , which is naturally found on raw and fermented meats ( 15 , 30 ). Despite being widely associated with animal muscle tissue and therefore, with food, it has also been isolated from chicken intestines ( 1 , 24 ), a finding that was confirmed in this study. While there have been numerous studies on L. sakei demonstrating its use as a protective culture for meat products ( 14 , 30 ), there have also been reports on its probiotic potential, especially in the poultry industry ( 22 , 24 ).…”
Section: Discussionsupporting
confidence: 83%
“…One of these bacteria is Lactobacillus sakei , which is naturally found on raw and fermented meats ( 15 , 30 ). Despite being widely associated with animal muscle tissue and therefore, with food, it has also been isolated from chicken intestines ( 1 , 24 ), a finding that was confirmed in this study. While there have been numerous studies on L. sakei demonstrating its use as a protective culture for meat products ( 14 , 30 ), there have also been reports on its probiotic potential, especially in the poultry industry ( 22 , 24 ).…”
Section: Discussionsupporting
confidence: 83%
“…(2019) suggested a protective effect of L. acidophilus , L. rhamnosus , and L. casei against Salmonella enterica Javiana . Ahmed et al. (2019) concluded that Lactobacillus species with PRO properties can be used in poultry feed formulation for their health benefits to combat gastrointestinal infections.…”
Section: Resultsmentioning
confidence: 99%
“… Li et al (2020) also found that Lactobacillus consisted in the gut of healthy pigs. Lactobacillus had a strong antibacterial activity, which enhanced the health of the chickens by inhibiting the growth of pathogens through competitive exclusion in the gastrointestinal tract ( Ahmed et al, 2019 ). In addition, dietary 3% HILM increased the genus Romboutsia , a valuable intestinal biomarker in maintaining the health of the host ( Mangifesta et al, 2018 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%